Impact assessment of battery energy storage systems towards achieving sustainable development goals. (October 2021) - Hannan, M.A.; Al-Shetwi, Ali Q.; Begum, R.A.; Jern Ker, Pin; Rahman, S.A.; Mansor, M.; Mia, M.S.; Muttaqi, K.M.; Dong, Z.Y.
Highlights: BESS utilization and its impact evaluation on achieving SDGs is investigated. SDGs were divided in environment, society, and economy based sustainable development. An expert elicitation method is used to analysis the BESS impacts on SDGs targets achievement. With the exponential growth of BESS, the impacts may cover additional targets in the future. BESS impact assessment claimed on the technology regulatory requisite for sustainable development. Abstract: Battery energy storage system (BESS) has many purposes especially in terms of power and transport sectors (renewable energy and electric vehicles). Therefore, the global demand for batteries is projected to rise by 25% per annum. In this context, given the recent sharp increase of BESS utilization and its progressing impact on the world energy sector, evaluation of its effect on achieving sustainable development goals (SDGs) is limitedly explored and must be investigated. This is a critical research gap, as we find that BESS may influence the ability to meet all SDGs. To assess the BESS impacts, 17 SDGs were divided into three groups, including environment, society, and economy as per the three key pillars of sustainable development. In assessing the BESS impacts, an expert elicitation model is used to show how the BESS affects the positive and negative impact on the 169 targets of 17 SDGs under the environment, society and economy group. We found that the BESS positively impacts the achievement of 60 targets (35.5%) of all SDGs, but it may negatively impact the accomplishment of 22 targets (13%). With the current development and exponential growth of BESS shares along with addressing certain present limitations, these impacts may cover additional targets in the future. However, present research foci neglect significant facets. Our assessment shows that the rapid growth and evolution of BESS must be accompanied by the requisite regulatory insight and technology regulation for sustainable development.